O estudo da formação dos conceitos científicos de matemática para alunos com autismo - Camargo, Erica Daiane Ferreira (2024)
Vygotsky's studies on concept formation show the complex activity involved in psychological functions, and that this acquisition is carried out through signs. It is an activity that is present at all stages, constituting the process of development and learning of subjects, a conception that establishes two types of concepts: spontaneous and scientific. For the theory, everyone can learn and develop, which is in line with the principles of inclusive education. The aim of this research is to build math teaching activities aimed at forming scientific concepts in students with autism in the school context. The focus of the research is on the area of mathematics, understanding that the area is important for the formation of subjects and development in the socio historical context. It is understood that mathematical literacy is the basis for developing the elaboration, applicability and interpretation of mathematical concepts in different situations. This is a qualitative study, which initially used exploratory research to investigate the school trajectories and math concepts acquired by the students with autism taking part in this study. Secondly, we used Activity Theory, which Leontiev postulated under the precepts of cultural-historical theory, to guide the development of pedagogical activities that lead to the formation of mathematical concepts for students with autism. The instruments used to collect the data were observation of the participants' development, dialog with the families and therapists of the children and adolescents, the application of a diagnostic math assessment and a spreadsheet with the selection of content by grade. The results include the understanding that the school trajectories of students with autism are marked by intercurrences generated by the barriers present in the educational inclusion process; that there is a gap between the year of enrollment and the development of learning in this area of knowledge; mathematical literacy can be a source of cognitive and social development and a basis for inclusion in the curriculum for students with autism; it is important to appropriate a methodological approach to guide the adaptation of teaching activities so that they result in the formation of scientific concepts of mathematics for students with autism enrolled in mainstream schools. The main result is the creation and organization of a database with mathematical activities for the 1st, 2nd and 3rd year of elementary school. The conclusion is that reflection and the implementation of new practices are essential if the school is to be a place for all students to learn and become truly inclusive.